Angiographic Quantitative Flow Ratio–Guided Treatment of Patients With Physiologically Intermediate Coronary Lesions - Jiannan Dai; Changdong Guan; Xueming Xu; Jingbo Hou; Haibo Jia; Huai Yu; Zening Jin; Guosheng Fu; Xiaofan Wu; Liansheng Wang; Rongchong Huang; Zhujun Shen; et al. (Journal of the American Heart Association: Cardiovascular and Cerebrovascular Disease)
Background The FAVOR III (Comparison of Quantitative Flow Ratio Guided and Angiography Guided Percutaneous Intervention in Patients With Coronary Artery Disease) China trial reported improved clinical outcomes with percutaneous coronary intervention guided by quantitative flow ratio (QFR) compared with angiography. Whether these benefits also apply for patients presenting with “uncertainty‐zone” lesions of intermediate physiological significance is uncertain. This study aims to examine the impact of QFR guidance versus angiography guidance on the management and outcomes of percutaneous coronary intervention in uncertainty‐zone lesions. Methods and Results In this prespecified subgroup analysis, offline QFR assessment categorized 873 patients (22.9%) into the uncertainty‐zone subgroup, defined as having an offline QFR of 0.75 to 0.85 in all coronary arteries with a lesion causing ≥50% diameter stenosis. At 2 years, the rate of major adverse cardiac events, a composite of all‐cause death, myocardial infarction, or ischemia‐driven revascularization, occurred in 31 patients (7.0%) in the QFR‐guided group and 35 patients (8.3%) in the angiography‐guided group (hazard ratio [HR], 0.85 [95% CI, 0.52–1.37]). In landmark analysis, the relative treatment effect of QFR guidance versus angiography guidance on major adverse cardiac events differed before 1 year (4.7% versus 3.8%; HR, 1.25 [95% CI, 0.65–2.40]) and after 1 year (2.3% versus 5.5%; HR, 0.41 [95% CI, 0.20–0.87]) (Pinteraction=0.03), driven by fewer nonprocedural myocardial infarctions and ischemia‐driven revascularizations in the QFR‐guided group after 1‐year follow‐up. Conclusions In the modest‐sized subgroup of patients with physiologically intermediate lesions randomized in the FAVOR III China trial, 2‐year clinical outcomes were not significantly improved with a QFR‐guided revascularization strategy compared with angiography guidance. Registration URL: https://www.clinicaltrials.gov; Identifier: NCT 03656848.